Association of pancreatic adenocarcinoma up-regulated factor expression in ovarian mucinous adenocarcinoma with poor prognosis - Kim, Sang Kyum (e-Century Publishing Corporation, 2014)
Pancreatic adenocarcinoma up-regulated factor (PAUF) expression is elevated in both ovarian tumors and pancreatic adenocarcinoma. However, PAUF expression in ovarian tumors according to histologic subtype and grade has not been investigated. In this study, we examined various clinicopathologic features of 24 patients with mucinous cystadenoma (MCA), 36 with mucinous borderline tumors (MBTs), and 46 with mucinous adenocarcinomas (MACs) according to PAUF expression status assessed using immunohistochemistry. We found that MACs more frequently stained positive for PAUF than did MCAs and MBTs (P < 0.0001). Although there was no significant differences with respect to other clinicopathologic characteristics of MACs according to PAUF expression status, patients with PAUF-weakly positive and PAUF-strongly positive MACs tended to have a shorter overall survival (OS) than those with PAUF-negative MAC, determined using a Kaplan–Meier analysis (P = 0.1885). After adjusting for various clinicopathologic parameters, PAUF positivity of MACs was a significant predictive factor for disease-free survival (DFS) (negative vs. weakly positive: P = 0.045, hazard ratio [HR] = 57.406, 95% confidence interval [CI]: 1.090-3022.596; and negative vs. strongly positive: P = 0.034, HR = 97.890, 95% CI: 1.412-6785.925). In conclusion, PAUF was more frequently expressed in MAC than in its benign and borderline counterparts, and was associated with a poor OS and DFS in MAC patients. Therefore, we suggest that PAUF may be a practical biomarker for histopathological categorization and a prognostic marker for patients with an ovarian mucinous tumor.